Elemental characterization of crystalline silicotitanate following Hanford tank waste processing. Issue 8 (24th May 2021) - Campbell, Emily L.; Westesen, Amy M.; Colon, Ferdinan C.; Boglaienko, Daria; Levitskaia, Tatiana G.; Peterson, Reid A.
ABSTRACT: To expedite vitrification of low activity waste at the Hanford Site, a Tank-Side Cesium Removal system, using crystalline silicotitanate (CST) as the ion exchange media, is being evaluated. Laboratory scale testing of Cs removal by CST from Hanford tank waste supernates has been conducted by Pacific Northwest National Laboratory. Selectivity and partitioning of analytes on spent CST, specifically RCRA hazardous metals, selected +2 cations, and transuranic elements, were characterized through the complete digestion of CST. The CST was shown to adsorb a relevant fraction of Ca, Cd, Pb, Sr, U, Pu, Np, Am, and potentially Fe by IX and/or other mechanisms.